Recognizing Physisorption and Chemisorption in Carbon Nanotubes Gas Sensors by Double Exponential Fitting of the Response - Calvi, Andrea (Sensors (Basel), 2016)
Multi-walled carbon nanotubes (CNTs) have been grown in situ on a [Formula: see text] substrate and used as gas sensors. For this purpose, the voltage response of the CNTs as a function of time has been used to detect [Formula: see text] and [Formula: see text] at various concentrations by supplying a constant current to the system. The analysis of both adsorptions and desorptions curves has revealed two different exponential behaviours for each curve. The study of the characteristic times, obtained from the fitting of the data, has allowed us to identify separately chemisorption and physisorption processes on the CNTs.